Magnetic Characterizations of Cobalt Oxide Nanoparticles - Koseoglu, Yuksel; Kurtulus, Figen; Kockar, Hakan; Guler, Halil; Karaagac, Oznur; Kazan, Sinan; Aktas, Bekir (Springer, 2012)
Cobalt oxide (Co3O4) nanoparticles were synthesized by a novel microwave-assisted decomposition reaction of the cobalt nitrate hexahydrate, Co(NO3)(2)a <...6H(2)O. While most of the traditional methods for the preparation of Co3O4 are at relatively high temperature, microwave-assisted decomposition was adapted to have better control in the production of Co3O4 nanoparticles. The temperature dependence of the magnetic properties for the Co3O4 was investigated by vibrating sample magnetometer (VSM) and electron spin resonance (ESR) techniques. VSM and ESR measurements have shown a phase transition occurring at around 31 K, as the antiferromagnetic transition temperature for the bulk Co3O4 crystal exhibits almost the same value. The average particle size of the sample at around the transition temperature is estimated as 2.015 nm. The title compound was characterized and identified by an x-ray powder diffraction (XRD).
International Conference on Nanoscale Magnetism (ICNM) -- SEP 28-OCT 02, 2010 -- Gebze-Istanbul, TURKEY
Keywords: Magnetic properties of nanostructures; Electron spin resonance (ESR); Antiferromagnetics